2023
DOI: 10.29333/ejmste/13428
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the potential of artificial intelligence tools in educational measurement and assessment

Valentine Joseph Owan,
Kinsgley Bekom Abang,
Delight Omoji Idika
et al.

Abstract: Artificial intelligence (AI) is transforming various industries, and education is no exception. Rapid advancements in AI technology have become essential for educators and educational assessment professionals to enhance teaching and learning experiences. AI-powered educational assessment tools provide numerous benefits, including improving the accuracy and efficiency of assessments, generating personalized feedback for students, and enabling teachers to adapt their teaching strategies to meet the unique needs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…These enhancements offer a more streamlined approach to resource management, allowing educators to devote their time to more meaningful educational activities. Using AI-driven insights, educational institutions can personalize educational materials to successfully address each student's unique needs, creating an environment that promotes academic and personal development [85]. Automating regular tasks such as grading, attendance monitoring, and scheduling increases operational efficiency and improves data management accuracy and reliability.…”
Section: Discussion and Implications Of The Integrative Literature Re...mentioning
confidence: 99%
“…These enhancements offer a more streamlined approach to resource management, allowing educators to devote their time to more meaningful educational activities. Using AI-driven insights, educational institutions can personalize educational materials to successfully address each student's unique needs, creating an environment that promotes academic and personal development [85]. Automating regular tasks such as grading, attendance monitoring, and scheduling increases operational efficiency and improves data management accuracy and reliability.…”
Section: Discussion and Implications Of The Integrative Literature Re...mentioning
confidence: 99%
“…As illustrated in Table 1, the median and interquartile range (IQR) per item for quality are presented. The MCQs exhibited a high median quality score of 24.5 (IQR: [22][23][24][25]. A comparison revealed that chatbotgenerated items had a median score of 25 (IQR: 21.25-25), slightly higher than the human-generated items which scored a median of 24 (22.25-25), however, this cannot be interpreted as superiority.…”
Section: Scoring Inferencesmentioning
confidence: 92%
“…From its integration into the teaching and learning environment, it uses as a collaboration coach, personal tutor, and study buddy to an ally for educators, to aiding in the design of educational material, and in our case -the development of assessment. In the eld of educational measurement and assessment, several authors (Khilnani, 2023;Owan et al, 2023) have proposed its use to ameliorate the workload of educators. However, using these types of tools requires evidences of validity before applying them in the educational context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given the typical lag between technological advancement and publishing research, very few generative AI studies have yet been published in measurement journals (although some exceptions include Zheng et al, 2023, which examined a Chinese composition tutoring system in the Chinese/English Journal of Educational Measurement and Evaluation; Zhang et al, 2022, a preprint that summarized current ChatGPT studies, including those relevant to testing; and Owan et al, 2023, which explained how ChatGPT and other artificial intelligence tools can be used in personalized teaching and automated grading). Most papers that currently exist are either preprints, white papers, or publications in journals that we did not consider for inclusion in this study (such as ML journals or educational technology journals).…”
Section: Special Comments On Generative Aimentioning
confidence: 99%